2013
DOI: 10.1242/jeb.093658
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow dynamics in the snake spectacle

Abstract: SUMMARYThe eyes of snakes are shielded beneath a layer of transparent integument referred to as the 'reptilian spectacle'. Well adapted to vision by virtue of its optical transparency, it nevertheless retains one characteristic of the integument that would otherwise prove detrimental to vision: its vascularity. Given the potential consequence of spectacle blood vessels on visual clarity, one might expect adaptations to have evolved that mitigate their negative impact. Earlier research demonstrated an adaptatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 31 publications
1
14
1
Order By: Relevance
“…The vascular lumens were not distinguishable by OCT at any time. In recent studies, van Doorn demonstrated that spectacular blood flow is low and variable in resting and undisturbed coachwhip snakes ( Masticophis flagellum , Colubridae), and becomes much increased and continuous during the integument renewal phase . This is concordant with our observations.…”
Section: Discussionsupporting
confidence: 92%
“…The vascular lumens were not distinguishable by OCT at any time. In recent studies, van Doorn demonstrated that spectacular blood flow is low and variable in resting and undisturbed coachwhip snakes ( Masticophis flagellum , Colubridae), and becomes much increased and continuous during the integument renewal phase . This is concordant with our observations.…”
Section: Discussionsupporting
confidence: 92%
“…Snakes possess a tertiary‐type spectacle that originates from the fusion of the upper and lower eyelid, thereby providing protection against injury and desiccation of the cornea, and allowing the snake to keep its eyes continuously open to detect predators and prey . Like other scales, the spectacle is vascularized and the cuticle of the spectacle is shed with the rest of the epithelium of the head during ecdysis. The spectacle also plays a critical optical role in refraction, almost equal to that of the lens .…”
Section: Introductionmentioning
confidence: 99%
“…The presence of blood vessels in the spectacle of snakes and the ability to constrict these vessels have previously been reported in detail . However, this study is the first to reflect on the importance of the location of the vessels within the spectacle stroma.…”
Section: Discussionmentioning
confidence: 56%
“…The position of vessels may influence the visual acuity of the snake. Species with slit pupils such as boas and pythons are speculated to be more susceptible to casting perceptible images of the spectacle vessels on the retina, whereas species with larger, round pupils such as many colubrids are less likely to perceive the spectacle vessels as entoptic phenomena . The location of the blood vessels of the spectacle in the middle or inner layers of the stroma may therefore be considered to be related to the area of minimal reflection of the vessels on the retina.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation